Adapting existing behaviour: perceptions of substance switching and implementation of minimum pricing for alcohol in Wales - Buhociu, Marian (2020)
Minimum Pricing for Alcohol (MPA) was enacted in Wales on March 2nd 2020. During the legislative process (i.e. consultation and parliamentary discussion), concern was expressed about the possibility of some drinkers switching to using other substances in response to any rise in the cost of alcohol. This paper reports on findings from a study which explored these pre-implementation concerns and how the policy was shaped. The research involved surveys (n=193) and interviews (n=87) with drinkers (predominantly harmful or treatment seeking) and providers of services. Survey responses were detailed, thus when combined with the interviews, provided a wealth of qualitative data, which are drawn upon in this paper. The findings highlight an expectation that most drinkers would respond to the new policy with adaptations of their coping mechanisms to maintain alcohol use at pre-legislative levels. This was either by switching alcohol products and adjusting their lifestyle to maintain an affordable drinking habit or developing new behaviours to manage additional costs. A small group of those with previous experience of drug use were identified as likely to switch from using alcohol to some other substances. Prior to the legislation being implemented awareness of the detail of the policy was found to be low, and perceptions of increased potential harm for certain groups were linked to concern about a lack of treatment capacity